Comparing the Contract Between Islamic and Indonesian Laws - Atharyanshah Puneri (Faculty of Law, University of Jember, Indonesia, 2020)
In the common transaction, the contract plays a crucial element made between the parties with their consent. Its importance reflects that the contract realizes the parties' agreements and the contract binds the parties mentioned in the agreements. This study aims to review the contract law by analyzing the law of contract from two different laws, which are Islamic and Indonesian laws. This study finds some similarities and differences between Islamic and Indonesian laws when they come to governing contracts. Every contract in Islamic law must comply with sharia aspects, and the law derived from the Quran and Hadith. Meanwhile, based on Indonesian law, a contract can be deemed legal when it complies with the requirements stated in Article 1320 Indonesian Civil Code, and every Contract in Indonesian Law comes and is derived from the Indonesian Civil Code. KEYWORDS: contract law, Islamic law, Indonesian law.